Lidar observation campaign of sugar cane fires and industrial emissions in the State of São Paulo, Brazil - Landulfo, E.; Jorge, Maria Paulete M. P.; Held, Gerhard [UNESP]; Guardani, Roberto; Steffens, Juliana; Dos Anjos F. Pinto, Sergio [UNESP]; Andre, Iara R. [UNESP]; Garcia, Gilberto [UNESP]; Lopes, F. J S; Mariano, Glauber L.; Da Costa, Renata F.; Rodrigues, Patricia F. (SPIE, the international society for optics and photonics, 2010)
Brazil has an important role in the biomass burning, with the detection of approximately 100,000 burning spots in a single year (2007). Most of these spots occur in the southern part of the Amazon basin during the dry season (from August to november) and these emissions reach the southeast of the country, a highly populated region and with serious urban air pollution problems. With the growing demand on biofuels, sugarcane is considerably expanding in the state of São Paulo, being a strong contributor to the bad air quality in this region. In the state of São Paulo, the main land use are pasture and sugarcane crop, that covers around 50% and 10% of the total area, respectively. Despite the aerosol from sugarcane burning having reduced atmospheric residence time, from a few days to some weeks, they might get together with those aerosol which spread over long distances (hundreds to thousands of kilometers). In the period of June through February 2010 a LIDAR observation campaign was carried in the state of São Paulo, Brazil, in order to observe and characterize optically the aerosols from two distinct sources, namely, sugar cane biomass burning and industrial emissions. For this purpose 2 LIDAR systems were available, one mobile and the other placed in a laboratory, both working in the visible (532 nm) and additionally the mobile system had a Raman channel available (607 nm). Also this campaign counted with a SODAR, a meteorological RADAR specially set up to detect aerosol echoes and gas-particle analyzers. To guarantee a good regional coverage 4 distinct sites were available to deploy the instruments, 2 in the near field of biomass burning activities (Rio Claro and Bauru), one for industrial emissions (Cubatão) and others from urban sources (São Paulo). The whole campaign provide the equivalent of 30 days of measurements which allowed us to get aerosol optical properties such as backscattering/extinction coefficients, scatter and LIDAR ratios, those were used to correlate with air quality and meteorological indicators and quantities. In this paper we should focus on the preliminary results of the Raman LIDAR system and its derived aerosol optical quantities. © 2010 Copyright SPIE - The International Society for Optical Engineering.
Keywords: aerosols; biomass burning; LIDAR; lidar ratio; scatter ratio; Aerosol optical property; Amazon basin; Atmospheric residence time; Dry seasons; Growing demand; Lidar observation; Lidar systems; Long distances; Mobile systems; Near fields; Optical quantities; Particle analyzer; Raman channel; Raman lidar system; Sugar cane fires; Sugarcane crops; Urban air pollution; Agriculture; Air quality; Atmospheric aerosols; Biomass; Industrial emissions; Meteorological radar; Optical properties; Remote sensing; Sugar cane; Sugars; Optical radar